Counseling-supportive interventions to decrease infertile women’s perceived stress: A systematic review - Yazdani, Fereshteh (Electron Physician, 2017)
BACKGROUND: Infertility all around the world and in every culture is recognized as a stressful and critical experience that threatens individual, familial, marital, and social stability. Thus, in accordance with the importance of a woman’s mental health and the possible impact of mental health on treatment outcome, finding a way to deal with perceived stress in women can help improve pregnancy outcomes. METHODS: This study is a systematic review on reducing perceived infertility stress in infertile women. The current study was undertaken using multiple databases such as SID, Irandoc, Magi ran, Google Scholar, PubMed, Science Direct, Scopus, Cochrane library, and CINAHL selected from articles pertinent to the study. The selection of papers was undertaken from 1990 through May 2016. The methodological quality was assessed. RESULTS: The initial search yielded a list of 725 papers, and then reviewers studied titles and abstracts. Thereafter, 68 papers were incorporated, and researchers reviewed summaries of all of the searched articles. Finally, the researchers utilized the data gained from 29 full articles so as to compile this review paper. Reviewing the studies conducted on reducing infertility perceived stress, the researchers classified related findings into two main categories: supportive and counseling intervention. CONCLUSION: Considering the fact that there is an international agreement that fertility centers need to offer counseling programs for psychological problems of the infertile, it is especially important to recognize counseling-supportive interventions for decreasing infertile women’s perceived stress and to program plans for decreasing women’s perceived stress. By investigating counseling-supportive stress, we hope that this study has stepped forward toward health care agent’s familiarity with decreasing infertile women’s perceived stress and, therefore, improving treatment consequences.